Nanotechnology and Ethics: The Role of Regulation Versus Self-Commitment in Shaping Researchers’ Behavior - Fink, Matthias (2012)
The governance of nanotechnology seeks to limit its risks, without constraining opportunities. The literature on the effectiveness of approaches to governance has neglected approaches that impact directly on the behavior of a researcher. We analyze the effectiveness of legal regulations versus regulation via self-commitment. Then, we refine this model by analyzing competition and autonomy as key contingency factors. In the first step, qualitative interviews with nanotechnology researchers are conducted to reflect this model. In the second step, its empirical relevance is tested using a survey of 90 nanotech researchers. The results indicate that legal regulations, as well as self-commitment to an informal CoC reduce the scope of behavior. Finally, that competition and autonomy affect the relative strength of these governance factors.